A Multigrid-Schwarz Method for the Solution of Hydrodynamics and Heat Transfer Problems in Unstructured Meshes - Galante, Guilherme; Rizzi, Rogerio L.; Diverio, Tiaraju A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2007)
This paper presents a parallel multigrid-Schwarz method for the solution of hydrodynamics and heat transfer problems. In the proposed method, the solution is obtained by a multigrid method parallelized by domain decomposition techniques, more specifically by the additive Schwarz method. The experiments performed have shown that the proposed implementation is computationally efficient, have good scalability, and good numerical quality.